PENGARUH LATIHAN AIR ALERT DAN PLYOMETRIC TERHADAP KEMAMPUAN DAYA LEDAK OTOT TUNGKAI PADA ATLET EKSTRAKURIKULER BASKET PUTRI SMAN 1 PEGANDON : Penelitian kuantitatif - M Bayu Nurdiansyah; Donny Anhar Fahmi; Fajar Ari Widiyatmoko (STKIP Subang, 2024)
As time goes by, basketball has become increasingly popular because it can be played in groups consisting of two teams of five people each. This study aims to determine the effect of Air Alert, Plyometric and Air Alert Plyometric exercises on leg muscle explosive power at SMA N 1 Pengandon. This research uses an experimental method with a Two Groups Pre-Test and Post-Test research design. Data was tested using the SPSS program. The tests carried out are normality, homogeneity and hypothesis testing. Based on the results of the data analysis that has been carried out, there is a significant influence between Plyometric and Air Alert training on the explosive power ability of leg muscles in female basketball extracurricular athletes at SMA N 1 Pegandon. This is because plyometric training trains power, where power is a combination of two elements, namely speed and strength. Apart from that, there is an influence of plyometric training on the explosive power ability of leg muscles in female basketball extracurricular athletes. In this study, it was also found that Air Alert training had no effect on the explosive power ability of leg muscles in female basketball extracurricular athletes. This is because Air Alert training is the same as Plyometrics. This research shows that there is an influence on Plyometric training and a combination of Plyometric and Air Alert training on the explosive power ability of leg muscles in female basketball extracurricular athletes at SMAN 1 Pegandon. As time goes by, basketball has become increasingly popular because it can be played in groups consisting of two teams of five people each. This study aims to determine the effect of Air Alert, Plyometric and Air Alert Plyometric exercises on leg muscle explosive power at SMA N 1 Pengandon. This research uses an experimental method with a Two Groups Pre-Test and Post-Test research design. Data was tested using the SPSS program. The tests carried out are normality, homogeneity and hypothesis testing. Based on the results of the data analysis that has been carried out, there is a significant influence between Plyometric and Air Alert training on the explosive power ability of leg muscles in female basketball extracurricular athletes at SMA N 1 Pegandon. This is because plyometric training trains power, where power is a combination of two elements, namely speed and strength. Apart from that, there is an influence of plyometric training on the explosive power ability of leg muscles in female basketball extracurricular athletes. In this study, it was also found that Air Alert training had no effect on the explosive power ability of leg muscles in female basketball extracurricular athletes. This is because Air Alert training is the same as Plyometrics. This research shows that there is an influence on Plyometric training and a combination of Plyometric and Air Alert training on the explosive power ability of leg muscles in female basketball extracurricular athletes at SMAN 1 Pegandon.